PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENT TEAMS ACHIEVEMENT DIVISION (STAD) UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS III. C SD NEGERI 133 PEKANBARU - Ulia, Fitri Ulia; Saragih, Sehatta Saragih; Solfitri, Titi Solfitri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: This research was based on the studentsâ achievement in learning mathematics especially grade III.C of SD N 133 Pekanbaru under the Mastery Minimum Criteria with percentage of 41.67% on the 1st Basic Competency and 36,11% on the 2nd Basic Competency. The teacher-centered learning was still used to teach materials during the learning process. The research conducted was the Classroom Action Research. The aims of this research is to improve the learning process and results on the students learning mathematic by implementing cooperative learning model Student Teams Achievement Division (STAD). There were 36 students in the class consisting 16 boys and 20 girls as the participant of this research. The instruments of data collection in this research were observation sheets and students Mathematic tests. The observation sheets were analyzed in qualitative desciptive, while the studentsâ Mathematic tests were analyzed in quantitative desciptive. The qualitative desciptive showed an improvement of learning process prior to the action on the first and second cycles. The results of this research showed an increasing number of students learning Mathematic from the basic scoreto the first test and second test.Based on the result of this research could be concluded that the implementation of Cooperative Learning Model Student Teams Achievement Division (STAD) can improve the studentâs achievement of learning Mathematic in grade III.C of SD N 133 Pekanbaru in the first semester academic years 2014/2015. Key Word : Studentâs Math Achievement, Cooperative Learning Model Student Teams Achievement Division (STAD), Clasroom Action Research Â Â